Implementasi Pembuatan Surat Izin Mengemudi Oleh Satuan Penyelenggara Administrasi Surat Izin Mengemudi Polisi Resor Kota Pagar Alam - Wita Hariani; Yohanes Susanto (STIA Bengkulu, 2023)
The purpose of this research is to find out the standard operating procedure for making a driver's license. The implementation of standard operating procedures in public services is one way to realize good governance in public services. As well as the importance of order and smooth traffic in order to avoid traffic accidents that can result in death, injury or damage and loss of property. So Law no. 22 of 2009 concerning Road Traffic and Transportation that everyone who owns a motorized vehicle is required to have a driving license in accordance with the type of motorized vehicle being driven as a legitimacy of the driver's competence. This research method is a qualitative research method with descriptive analysis techniques. Techniques Data collection is done by interview, observation and documentation. Determination of informants based on purposive technique. For the aspect of completion time is less than the standard time set. The standard service completion time is two hours, but the implementation is less than two hours because there are several processes that are not carried out such as written tests and practical tests. The cost aspect of making a driving license is greater than the provisions stipulated in PP no. 50 of 2010 concerning PNBP. This is because of the system for making a Shooting Driver's License. For the aspect of competence of service providers as well as aspects of the completeness of facilities and infrastructure are sufficient.